2011
DOI: 10.1111/j.1439-0469.2011.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

A new taxonomic status for Iberoformica (Hymenoptera, Formicidae) based on the use of molecular markers

Abstract: The subgeneric subdivision of the genus Formica is still open. In this article, we make a phylogenetic study on several species of the genus Formica and of its closely related genera, Polyergus and Proformica, using sequences of nuclear satellite DNA (stDNA) and the mitochondrial rrnL as molecular markers. Our goal was to shed light on their phylogenetic relationships and particularly on the systematic position of F. subrufa. This species was first included in the subgenus Serviformica, but afterwards a new su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Muñoz‐López et al. () found similar results for the slave‐making ants Polyergus and its host genus Formica , which agrees with the conclusion of Huang and Dornhaus () that slave‐making ants usually parasitize hosts from the same tribe and a close genus. Furthermore, our results stress the importance of including the genus Rossomyrmex in any phylogeny of Cataglyphis because its absence or presence influences the monophyletic status of the latter as well as the relationships among the different species groups.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Muñoz‐López et al. () found similar results for the slave‐making ants Polyergus and its host genus Formica , which agrees with the conclusion of Huang and Dornhaus () that slave‐making ants usually parasitize hosts from the same tribe and a close genus. Furthermore, our results stress the importance of including the genus Rossomyrmex in any phylogeny of Cataglyphis because its absence or presence influences the monophyletic status of the latter as well as the relationships among the different species groups.…”
Section: Discussionsupporting
confidence: 76%
“…Ants of the tribe Formicini (subfamily Formicinae) are the most conspicuous element of the Holarctic myrmecofauna (Dlussky, ) and include eight extant genera: Alloformica , Bajcaridris , Cataglyphis , Formica , Iberoformica , Polyergus , Proformica, and Rossomyrmex (Agosti, ; Muñoz‐López et al., ; Ward, Blaimer, & Fisher, ). Within this tribe, there are two genera of obligate slave makers: Polyergus and Rossomyrmex .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later study previous results were confirmed, and Iberoformica was raised to a genus status only composed by I. subrufa. In the present study a phylogenetic study was carried out on several species of the genus Formica and of its outgroup genera, Polyergus and Proformica, using sequences of nuclear satellite DNA and the mitochondrial 16S rRNA as molecular markers (Muñoz-López & al. 2012).…”
Section: Genetic Evidencementioning
confidence: 99%